Flavour volatile constituents and the roasting of selected spices - 332825 Amal Gasim Ahmed; Abu Bakar Baba, supervisor; Fakulti Sains (Skudai : Universiti Teknologi Malaysia, 1998)
Thesis (Master of Science (Chemistry)) - Universiti Teknologi Malaysia, 1998